Assessment of iris vasculature in type 2 diabetes mellitus patients without diabetic retinopathy using anterior segment optical coherence tomography angiography - Yue Zhou; Ting Wang; Zhenhuan Guo; Fan She; Jiahui Zeng; Xiaoyu Zhu (Scientific Reports)
Abstract To investigate early changes of iris vasculature in type 2 diabetes mellitus (T2DM) patients without diabetic retinopathy (DR) using anterior segment optical coherence tomography angiography (AS-OCTA), and evaluate potential predictors associated with iris vasculature in this population. This was a cross-sectional study. T2DM patients and healthy controls were patients who visited the Department of Ophthalmology at the Affiliated Hospital of Yangzhou University. Iris vessel density (IVD) was quantified using AS-OCTA (YG-100KPRO, TowardPi Medical Technology, Beijing, China). IVD was also performed in the whole and four quadrant sectors of iris, that is nasal superior (NS), nasal inferior (NI), temporal superior (TS), and temporal inferior (TI) sectors. Thirty-six patients with T2DM and thirty-nine healthy controls were recruited in this study. IVD in T2DM patients was lower than in healthy groups, particularly in the whole iris (P = 0.016) and the NI (P = 0.022) and TI (P = 0.007) sectors of the iris. Male gender was a positive independent predictor of IVD, whereas body mass index and blood glucose were negative independent predictors of IVD. AS-OCTA provides a reliable method to quantify iris blood flow. Our study reveals the deterioration of the iris vascular system in patients with T2DM, even without DR. These findings highlight the significance of iris blood flow parameters in T2DM patients, which could be helpful in follow-up studies and future screening for ocular vascular diseases associated with T2DM.